INTEGRATED REPORTING IN THE CONTEXT OF KEY STAKEHOLDER INFORMATION SUPPORT - Shkromyda , V.V.; Shkromyda , N.Ya.; Gnatyuk , T.M. (The actual problems of regional economy development, 2022)
Traditional financial statements, in their form and content, have ceased to meet the information needs of users of accounting information in today's business environment, as it contains data only on the historical facts of the financial condition of the enterprise and its results. In addition to the demand for financial indicators, there is a significant focus on non-financial information from key stakeholders. In other words, the stakeholders of the existing business want to be informed about the social significance, environmental sensitivity, future results, as well as the risks and opportunities of the business entity in the future. Of course, achieving this goal is possible through the implementation of integrated reporting companies. The aim of the study is to substantiate the theoretical and organizational basis for the implementation of integrated reporting in the context of information support of key business stakeholders through the disclosure of its historical features at the international level and search for approaches to implementing experience in domestic accounting and analytical practice. Certainly, the promotion and standardization of integrated reporting by different institutions has achieved two important goals. The first is to increase the attention of both large and small businesses to sustainable development, as companies are actively committed to achieving their own social and environmental performance in the context of the interests of key stakeholders. Under such conditions, business becomes indifferent to the environment, social justice and prospects for future generations. Achieving the second goal provides a gradual expansion of opportunities for the existing system of accounting and reporting. After all, such circumstances expand the boundaries of accounting observation, give rise to the search for methods of valuation of new objects, as well as contribute to the improvement of accounting approaches and their reflection in the reporting. The practical value of the research is to supplement the theoretical and methodological basis of integrated reporting, in terms of its historical transformation at the international level and the introduction of best practices in domestic accounting and analytical practice. The obtained scientific results will contribute to the development of the system of accounting and analytical reflection of the company's resources and the results of its activities related to the solution of socially important environmental and social issues.